Additives improve the enzymatic synthesis of biodiesel from waste oil in a solvent free system. (15th April 2015) - Nie, Kaili; Wang, Meng; Zhang, Xin; Hu, Wenjing; Liu, Luo; Wang, Fang; Deng, Li; Tan, Tianwei
Highlights: Biodiesel was synthesized in solvent free system with waste cooking oil. Cyclodextrin was introduced as additive to enhance the biodiesel yield. Only 0.4 wt% lipase Candida sp. 99–125 was enough for 1 ton biodiesel production. Lipase could also be reused for 5 times. By the assistant function of additive, the cost of lipase was reduced to 80 CNY. Abstract: Biodiesel production from waste oil by lipase Candida sp. 99–125 assisted with cyclodextrin as additive was investigated in a solvent free system. The optimum reaction conditions was determined toward lipase dosage, agitation speed, cyclodextrin loading, water content and reuse ability of free lipase. A certain dosage of cyclodextrin showed a significant improvement of the reactions. However, the agitation speed should not be too high, to avoid breaking the weak bond between cyclodextrin and lipase. The optimal conditions were: free lipase dosage 70 U/g oil (about 0.4 wt% to the oil weight, when activity of lipase was 20, 000 IU), cyclodextrin to lipase 2:1(g/g), water content 2 wt% (water/oil, g/g), and agitation speed 180 rpm. Methanol was added 30 times at 1/30 M equivalent each hour. Under the optimal conditions, the yield of FAMEs achieved 88%. After 5 cycles of reuse, no significant decrease in FAMEs yield was observed. The process has been successfully carried out at industrial scale in Shanghai, China.